Cost and energy intensity of U.S. potable water reuse systems. Issue 4 (22nd February 2021) - Sim, Alison; Mauter, Meagan S.
Abstract : We present a dataset of 70 operating, demonstration, pilot and unbuilt U.S. potable water reuse systems and report on treatment train designs, costs, estimated electricity intensity, and air emission externalities. Abstract : This paper reports on a new and open-source dataset, curated from facility-specific engineering reports, that details facility features for an aggregated total of 70 operating, demonstration, pilot and unbuilt U.S. potable water reuse systems. The dataset and our following analysis reviews treatment train design, estimated electricity consumption, facility capital and operation and maintenance costs, and air emission externalities of those systems. Despite a wide variety of feedwater qualities and augmentation strategies, we observe remarkable consistency in potable reuse treatment train design. We estimate potable reuse electricity intensity for each facility as a function of feedwater quality and installed unit processes, finding that advanced treatment train electricity intensities fall within the range of 0.23–2.5 kWh m −3 . This range excludes the energy required for conveying water to advanced treatment facilities or pumping the water for supply augmentation. For 25 facilities with capital cost data, we find that potable reuse capital costs normalized by system design capacity fall between 1000 and 5300 per m 3 d. Subsequent cost analysis of the subset of full advanced treatment (FAT) systems suggests capacity normalized capital costs between 1800 and 4100 per m 3 d and capacity normalized operation and maintenance costs between 100 and 200 per m 3 d. These ranges validate previously reported bottom-up cost estimates for FAT facilities. Finally, we use the Water AHEAD model to estimate the annual human health, environmental, and climate damages for representative advanced treatment trains. Air emission externalities from U.S. potable reuse facilities fall between 10 and 40 per thousand m 3, with the majority of damages associated with electricity consumption at potable reuse facilities.